Detection and quantification of hepatitis E virus genome in pig liver samples originating from Serbian retail establishments. Issue 1 (October 2021) - Milojevic, L; Velebit, B; Dimitrijevic, M; Djordjevic, V; Jankovic, V; Grkovic, N; Nikolic, A
Abstract: Hepatitis E is considered an emerging human viral disease with a zoonotic nature, and domestic and wild pigs are the main reservoirs of hepatitis E virus (HEV) among animals. Pork liver is the target tissue of this virus. This study aimed to investigate the presence of HEV in commercial pig liver samples. Sixty samples were collected during one year from different retail outlets in Serbia. Furthermore, the collected samples were separated by four seasons, and every season included three months. The presence of HEV in the livers was examined by molecular analysis using RT-qPCR. The overall prevalence of the virus in analysed pig livers was 5%. HEV was detected in three livers, two in the first season and one in the second, while in the third and fourth season, no positive livers were detected. However, there were no statistically significant differences between the surveyed seasons. HEV was quantified in positive livers. Among positive livers, HEV concentrations ranged between 8×10 1 and 1.9×10 4 genome copies of the virus per gram. The presence of HEV in commercial pig livers indicates a potential risk for consumers. Appropriate heat treatment of meals during preparation is essential to eliminate the potential risk of developing the illness.